2014
DOI: 10.3329/birdem.v4i1.18549
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Nurses’ Knowledge Regarding Prevention and Management of Diabetic Foot Ulcer in Bangladesh

Abstract: Diabetic foot ulcer is a preventable complication of diabetes. Nurses must have knowledge related to this condition so that education can be given to patients. This study aims to examine the level of nurses' knowledge regarding prevention and management of diabetic foot ulcer in Bangladesh. A survey involved 218 nurses working at a national, specialized, and well-established institute of diabetic care of Bangladesh. The Nurses' Knowledge Regarding Prevention and Management of Diabetic Foot Ulcer Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 9 publications
1
13
1
Order By: Relevance
“…Most studies on pressure ulcer prevention and care have reported comparable results (Nuru et al., ; Uba et al., ). Very low knowledge on diabetic ulcer disease reported in a survey conducted in Bangladeshi nurses can be attributed to their lack of training and knowledge update (Sharmisthas et al., ). Also, surprisingly low knowledge scores were reported in Jordanian nurses, although all of them were degree holders (Qaddumi & Khawaldeh, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies on pressure ulcer prevention and care have reported comparable results (Nuru et al., ; Uba et al., ). Very low knowledge on diabetic ulcer disease reported in a survey conducted in Bangladeshi nurses can be attributed to their lack of training and knowledge update (Sharmisthas et al., ). Also, surprisingly low knowledge scores were reported in Jordanian nurses, although all of them were degree holders (Qaddumi & Khawaldeh, ).…”
Section: Discussionmentioning
confidence: 99%
“…MCQs had three answer options, “true,” “false” and “do not know.” The third option was included to minimise guessing and to prevent leaving questions unanswered (Qaddumi & Khawaldeh, ). When scoring, correct answers scored 1 point each, while incorrect answers and “do not know” options scored zero (Sharmisthas et al., ). The total number of correct answers was computed to a percentage score and categorised according to McDonald's standard learning outcome measured criteria (McDonald, ) to evaluate the knowledge level of nurses (Uba et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations